Ustory-Refactory: ferramenta de refatoração de requisitos aplicada em cartões user stories (CRC Cards) - Minuzzi, Tiago da Silva (Universidade do Vale do Rio do Sinos, 2007)
The emergence of new agile methodologies to support systems development, as the Extreme Programming (XP), has been causing impact on software development companies, specially for its flexibility in the requirements changes during the project. Thus, a better understanding and structural representation of the requirements become basic. Then, this research applies the concept of the code refactoring techniques, inside of the Requirements Engineering, which is focused at XP methodology, through the User Stories. The work applies a set of standards and rules that allows the requirements expressed in CRC cards to be refactored through pre and post-conditions, and the requirements are described for conceptual maps (CMaps) in OWL format. In their turn, the CMaps are converted into UML classes diagrams by the UML-MC that formalizes this transformation. This way, the UStory-Refactory environment partially automatizes the refactoring process and allows the refactored requirements to be exported in OWL format, promoting
Keywords: engenharia de requisito; programação extrema; refatoração; software; XP; engenharia; engineering requirement; extreme programming; refactoring; ontology; software engineering; UML; Ciências Exatas e da Terra